Ras p21 in breast tissue: associations with pathology and cellular localisation. - Going, J. J. (Nature Publishing Group, 1992)
Immunocytochemistry with monoclonal antibody Y13-259 demonstrated p21 ras in paraffin sections of breast tissue from 171 women: 85 with invasive breast carcinoma, 14 with non-invasive carcinoma and 72 with benign changes only. Many different tissue elements contributed to ras expression. Semiquantitative assessment showed that intensity of immunostaining in the normal epithelium of large ducts, small extralobular ducts and terminal duct lobular units (TDLU) was usually exceeded by that of myoepithelial cells. Vascular smooth muscle and apocrine epithelium also stained strongly, but the flat epithelial cells lining cysts did not express detectable p21 ras. There was a progressive increase from normal epithelium through epithelial hyperplasia of usual type and atypical hyperplasia to carcinoma in situ, without further increase in invasive carcinoma. Expression in carcinomas was inversely related to oestrogen receptor content but independent of the prognosis-associated variables of size, histological type, vascular invasion or lymph node metastasis. IMAGES: